Pengaruh Kualitas Pelayanan terhadap Loyalitas Pelanggan dimediasi Kepuasan Pelanggan Pengguna Jasa Cargo - Lestari, I Gusti Ayu Asri Leony Putri; Susanti, Putu Herny; Abiyoga V.S, Ni Nyoman Adityarini (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to find out how the influence of service quality on customer satisfaction and loyalty. This research was conducted at PT. Khrisna Multi Sarana Indonesia Bali Branch. The number of samples taken were 96 respondents. Data collection techniques are observation, interviews, documentation, literature and questionnaires. The research instrument test uses validity and reliability tests. While the data analysis technique is by path analysis and sobel test. The test results show that service quality has a positive and significant effect on customer loyalty at PT. Khrisna Multi Sarana Indonesia Bali Branch. Service quality has a positive and significant effect on customer satisfaction at PT. Khrisna Multi Sarana Indonesia Bali Branch. Customer satisfaction has a positive and significant effect on customer loyalty at PT. Khrisna Multi Sarana Indonesia Bali Branch. Customer satisfaction is able to mediate the effect of service quality on customer loyalty at PT. Khrisna Multi Sarana Indonesia Bali Branch. The suggestion of this research is that it is hoped that the company will emphasize more so that employees are more patient in dealing with customer complaints, especially regarding the arrival time of cargo.